Prevention of Venous Thromboembolism in Medical Patients with Thrombocytopenia or with Platelet Dysfunction: The Last 10 Years - Tufano, Antonella; Brenner, Benjamin (Seminars in Thrombosis and Hemostasis, 2023)
Current guideline recommendations for primary prophylaxis of venous thromboembolism (VTE) are based on randomized clinical trials that usually exclude subjects at a potentially high risk of bleeding complications. For this reason, no specific guideline is available for thromboprophylaxis in hospitalized patients with thrombocytopenia and/or platelet dysfunction. However, except in patients with absolute contraindications to anticoagulant drugs, antithrombotic prophylaxis should always be considered, for example, in hospitalized cancer patients with thrombocytopenia, especially in those with multiple VTE risk factors. Low platelet number, platelet dysfunction, and clotting abnormalities are also very common in patients with liver cirrhosis, but these patients have a high incidence of portal venous thrombosis, implying that cirrhotic coagulopathy does not fully protect against thrombosis. These patients may benefit from antithrombotic prophylaxis during hospitalization. Patients hospitalized for COVID-19 need prophylaxis, but frequently experience thrombocytopenia or coagulopathy. In patients with antiphospholipid antibodies, a high thrombotic risk is usually present, even in the presence of thrombocytopenia. VTE prophylaxis in high-risk conditions is thus suggested in these patients. At variance with severe thrombocytopenia (< 50,000/mm3), mild/moderate thrombocytopenia (≥ 50,000/mm3) should not interfere with VTE prevention decisions. In patients with severe thrombocytopenia, pharmacological prophylaxis should be considered on an individual basis. Aspirin is not as effective as heparins in lowering the risk of VTE. Studies in patients with ischemic stroke demonstrated that thromboprophylaxis with heparins is safe in these patients also during antiplatelet treatment. The use of direct oral anticoagulants in the prophylaxis of VTE in internal medicine patients has been recently evaluated, but no specific recommendation exists for patients with thrombocytopenia. The need for VTE prophylaxis in patients on chronic treatment with antiplatelet agents should be evaluated after assessing the individual risk of bleeding complications. Finally, the selection of patients who require post-discharge pharmacological prophylaxis remains debated. New molecules currently under development (such as the inhibitors of factor XI) may contribute to improve the risk/benefit ratio of VTE primary prevention in this setting of patients.
Keywords: venous thromboembolism; prophylaxis; thrombocytopenia; low-molecular-weight heparin